PENGARUH PENDEKATAN MINDFULNESS TERHADAP KECEMASAN MATEMATIKA SISWA KELAS III DI SD NEGERI TANABANGKA KABUPATEN GOWA - Inayah Tul Aini; Bhakti Prima Findiga Hermuttaqien; Siti Zahra Mulianti Natsir (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Mathematics, learned from an early age to adulthood, plays an important role in daily life, especially in academics. However, many students perceive mathematics as difficult and intimidating, which can lead to mathematics anxiety. This study aimed to examine the effect of the mindfulness approach on students’ mathematics anxiety. The participants consisted of two groups: an experimental group and a control group, each with 20 students. Data were collected using a mathematics anxiety questionnaire and an observation sheet of learning implementation. The results showed a decrease in mathematics anxiety in the experimental group after receiving mindfulness treatment. This was indicated by a shift in anxiety levels from predominantly moderate to low. Meanwhile, the control group showed no significant change. Hypothesis testing using an independent sample t-test revealed a significance value (Sig. 2-tailed) of less than 0.05, indicating that Ha was accepted and H₀ was rejected. This means there was a significant difference in mathematics anxiety between the experimental and control groups after treatment. It can be concluded that the mindfulness approach significantly reduces mathematics anxiety among third-grade students at SD Negeri Tanabangka, Gowa Regency.